An Exploration on Pilots and Student Pilots Perspectives towards the Gender Bias in Thai Aviation Industry - Chanikarn Thatchatham; Waralee Peetawan (My University, 2020)
Since the aviation industry is acknowledged as the male-dominated filed, the existence of female pilots in the cockpit has long been controversial over decades. However, it is revealed by many aviation organizations that the number of women pilots has been growing constantly recently. Several studies have been conducted to explore female pilots' perspective towards the existing gender bias in the aviation field in the global scale. Meanwhile in Thailand, there is the scarcity of studies on the similar topic, especially perspectives towards the factors and motivations driving female pilot to enter the aviation industry in Thailand. This study purposes to investigate the perspectives of female student pilots, a female pilot and a male pilot towards the negative gender stereotypes in the pilot profession in Thai context. A mixed-method questionnaire was conducted to collect data by having two main approaches: a Likert-scale and close-ended questionnaire and the semi-structured interview from eight participants including six female student pilots (FSP), one female professional pilot (FP) and one male professional pilot (MP). The results yielded from all female participants revealed that gender prejudice still exists in the industry, which resulted in female pilots having to prove themselves and their skills set to be accepted in both the training duration and working period. However, all participants all opine that the aviation industry has recently seen the lesser degree of sexual bias towards female pilots and the positive trend of more female pilots stepping into this male-dominated field.
Keywords: Cockpit; Aviation Industry Analysis and Trends